Motivations and Intentionality in the Arts Portfolio Career - Karen Munnelly (Artivate, 2022)
Many artists find themselves in the role of an entrepreneur and small business owner as they manage multiple overlapping jobs while engaging in a portfolio career. This research investigates how visual and performing artists construct meaningful portfolio careers and if the portfolio career model minimizes risk. The findings reveal that the majority of respondents view a portfolio career as less secure than a full-time job, but also prefer the portfolio career. A significant amount of their time is spent on creative activity and teaching. Artistic fulfillment, pay, and time commitment are the primary factors artists consider when selecting work.